Non-LTE radiative transfer simulations: improved agreement of the double detonation with normal Type Ia supernovae - Collins, Christine E.; Shingles, Luke J; Sim, Stuart A; Callan, Fionntan P; Gronow, Sabrina; Hillebrandt, Wolfgang; Kromer, Markus; Pakmor, Rüdiger; Röpke, Friedrich (Monthly notices of the Royal Astronomical Society, 2025)
The double detonation is a widely discussed explosion mechanism for Type Ia supernovae, whereby a helium shell detonation ignites a secondary detonation in the carbon/oxygen core of a white dwarf. Even for modern models that invoke relatively small He shell masses, many previous studies have found that the products of the helium shell detonation lead to discrepancies with normal Type Ia supernovae, such as strong Ti ii absorption features, extremely red light curves, and too large a variation with viewing direction. It has been suggested that non-local thermodynamic equilibrium (non-LTE) effects may help reduce these discrepancies between observations. Here we carry out full non-LTE radiative transfer simulations for a recent double detonation model with a relatively small helium mass of 0.05 ${\rm M}_{\odot}$. We construct 1D models representative of directions in a 3D explosion model to give an indication of viewing angle dependence, and show that at early times up to around maximum light, this gives a reasonable approximation of the different directions in the 3D model. This approximation breaks down once the ejecta start to become optically thin. The full non-LTE treatment leads to improved agreement between the models and observations. The light curves become less red, due to reduced absorption by the helium shell detonation products, since these species are more highly ionized. Additionally, the expected variation with observer direction is reduced. The full non-LTE treatment shows promising improvements and reduces the discrepancies between the double detonation models and observations of normal Type Ia supernovae.